Keys for identification of immature insects - Thyssen, Patricia J. [UNESP] (Springer Nature, 2010)
The study of immature insects is important in forensic entomology, because the identification of the involved species is a crucial step in calculating the post-mortem interval (PMI) and because it is the insect life stage most frequently collected from corpses. The immature stage consists of the egg, nymph or larva with its average of three or four development instars, and the pupa. Decomposition of a dead body starts through the action of bacteria and fungi, followed by the action of a series of arthropods with a predominance of the dipteran insects (e.g., Carvalho et al. 2000, 2004). Therefore, the anatomical features of the immature stages of these insects are described and taxonomic keys utilized to identify order, family, and species of most of Brazil forensic relevant insects, with emphasis on larvae of the major Diptera families, are presented. Decomposition of a dead body starts through the action of bacteria and fungi, followed by the action of a series of arthropods with a predominance of the dipteran insects (e.g., Carvalho et al. 2000, 2004). Therefore, the anatomical features of the immature stages of these insects are described and taxonomic keys utilized to identify order, family, and species of most of Brazil forensic relevant insects, with emphasis on larvae of the major Diptera families, are presented.